Bipolar Saline TURP for Large Prostate Glands. (2007) - Finley, David S.; Beck, Shawn; Szabo, Richard J.
Abstract : The objective of this study was to evaluate the feasibility of bipolar transurethral resection of the prostate (TURP) in patients with very large prostate glands and significant comorbidities. Four patients with prostate glands >160 cc on preoperative volume measurement and ASA class three or higher underwent bipolar TURP with the Gyrus PlasmaKinetic system. Preoperative, operative, and postoperative parameters were studied. The results showed an average ASA class 3.25 (range: 3–4). The average preoperative prostate volume was 207.4 cc (range: 163–268). The average preoperative International Prostate Symptom Score (IPSS) and bother score was 31 and 6, respectively. Mean resection time was 163 min (range: 129–215). The weight of resected tissue and percentage of vaporized tissue was 80.8 g (range: 62–115) and 10.0% (range: 3.8–15.1), respectively. An average of 61L of saline was used (range: 48–78). The mean change in hemoglobin and serum sodium was 2.1 g/dl (range: 1.4–2.7) and 3.3 meq/l (range: 2–4), respectively. Postoperative catheter time averaged 76 h (range: 40–104). Mean length of hospital stay was 12 h (range: 4–24). The mean postoperative IPSS and bother score was 2.75 and 0.25, respectively. Bipolar TURP is a feasible alternative to simple open prostatectomy in high-risk patients with massive prostate adenomas. Prostate volume is reduced by approximately 10% due to vaporization.